2020
DOI: 10.1016/j.iref.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate pass-through & management of inflation expectations in a small open inflation targeting economy

Abstract: In the context of inflation targeting, this study analyses the exchange rate pass-through (ERPT) to inflation expectations in a small open inflation targeting economy. We also augment the inflation expectations function with GDP, inflation, unemployment, fiscal stance, oil prices and money supply. Drawing on the data from May 1999 to Dec 2018 on the Czech Republic, which was the first developing country to adopt inflation targeting, our key results suggest that ERPT has significant implications for inflation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…(2013) , Bahmani-Oskooee and Fariditavana (2015 , 2016) and most recently Nasir et al. (2020a , 2020b) to employ the NARDL model for our analysis. q t in the linear ARDL model in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…(2013) , Bahmani-Oskooee and Fariditavana (2015 , 2016) and most recently Nasir et al. (2020a , 2020b) to employ the NARDL model for our analysis. q t in the linear ARDL model in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Exchange rate (Exch): Gali and Monacelli (2005) argue that there could be a trade-off between nominal exchange-rate stability and price stability in a small open economy. Nasir et al (2020) use data from the Czech Republic to provide support of an "exchange-rate pass through" mechanism, through which the exchange rate can generate inflationary expectations and, hence, raise the prices of goods and services. In addition, Sims (1992) points out that the inclusion of exchange-rate variables in VAR models makes price "puzzle" responses to disappear.…”
Section: Expanded Meta-regression Analysis Explanatory Variablesmentioning
confidence: 99%
“…There is a substantial amount of literature on the impact of exchange rate dynamics on inflation, including the evidence on the UK (for instance, see Menon, 1995;Goldberg and Knetter, 1997;Hänninen and Toppinen, 1999;Campa and Goldberg, 2005;Choudhri and Hakura, 2006;Bache, 2006;Mumtaz et al, 2006;Bhattarai, 2011;Wimanda et al 2011;Burnstein and Gopinath, 2013;Forbes, 2014;Forbes, 2016;2015a;Yildirim and Ivrendi, 2016;Nasir and Simpson, 2018;Nasir and Vo, 2020;Nasir et al 2020aNasir et al , 2020b. Despite the substantial evidence on the subject, the existing models and estimates have substantial limitations and particularly when it comes to UK data on the exchange rate pass-through there are major divergences between the prevailing wisdom on the nexus between inflation and exchange rate and what is actually observed.…”
Section: Exchange Rate Pass-through To Inflationmentioning
confidence: 99%
“…It is prima facie evident that the forecast did not take into account the depreciation of Sterling. There is a vast empirical literature on the pass-through of exchange rates depreciation (See Menon, 1995;Goldberg and Knetter, 1997;Hänninen and Toppinen, 1999;Campa and Goldberg, 2005;Choudhri and Hakura, 2006;Bache, 2006;Mumtaz et al, 2006;Burnstein and Gopinath, 2013;Forbes, 2016;2015a;Nasir and Simpson 2018;Nasir and Vo 2020;Nasir et al 2020aNasir et al , 2020b) which showed various degrees of impact of exchange rates on inflation. Interestingly, the BoE herself has estimated the exchange rate pass-through, and in Forbes (2016) words:…”
Section: Introductionmentioning
confidence: 99%